Potential Research Tool of Stem Cells from Human Exfoliated Deciduous Teeth: Lentiviral Bmi-1 Immortalization with EGFP Marker. (10th March 2019) - Yao, Siqi; Tan, Lingping; Chen, Huan; Huang, Xiaojun; Zhao, Wei; Wang, Yan
Abstract : Stem cells from human exfoliated deciduous teeth (SHED) are a favourable source for tissue engineering, for its great proliferative capacity and the ease of collection. However, the transplantation of stem cells and the study of stem cell-based tissue engineering require massive stem cells. After long-term expansion, stem cells face many challenges, including limited lifespan, senescence, and loss of stemness. Therefore, a cell line capable of overcoming those problems should be built. In this study, we generated a Bmi-1-immortalized SHED cell line with an enhanced green fluorescent protein (EGFP) marker (SHED-Bmi1-EGFP) using lentiviral transduction. We compared this cell line with the original SHED for cell morphology under a microscope. The expression of Bmi-1 was detected with Western blot. Replicative lifespan determination and colony-forming efficiency assessment were using to assay proliferation capability. Senescence-associated β -galactosidase assay was performed to assay the senescence level of cells. Moreover, multipotency, karyotype, and tumour formation in nude mice of SHED and SHED-Bmi1-EGFP were also tested. Our results confirmed that Bmi-1 immortalization did not affect the main features of SHED. SHED-Bmi1-EGFP could be passaged for a long time and stably expressed EGFP. SHED-Bmi1-EGFP at a late passage showed low activity of β -galactosidase and similar multilineage differentiation as SHED at an early passage. The immortalized cells had no potential tumourigenicity ability in vivo . Moreover, we provided some suggestions for potential applications of the immortalized SHED cell line with the EGFP marker. Thus, the immortalized cell line we built can be used as a functional tool in the lab for long-term studies of SHED and stem cell-based regeneration.